The moderating role of dysphoria in the relationship between intrusions and alcohol use. (April 2016) - Contractor, Ateka A.; Presseau, Candice; Capone, Christy; Reddy, Madhavi K.; Shea, M. Tracie
Abstract: Posttraumatic Stress Disorder (PTSD) is frequently comorbid with alcohol use disorders (AUD; Calabrese et al., 2011; McFall, Mackay, & Donovan, 1992). Among several explanations for this comorbidity, the most empirically supported is the self-medication theory which postulates that substances are used to medicate PTSD-related distress (Keane & Wolfe, 1990; Khantzian, 1985; Stewart, 1996). The current study examines the effects of trauma-related distress on alcohol use (total drinking days, drinks per drinking day, heavy drinking days) in a sample of 127 trauma-exposed Veterans following deployment to Iraq or Afghanistan. The dysphoria symptoms of PTSD were used as an indicator of distress, and examined as a moderator in the relationship between intrusion symptoms of PTSD and alcohol use. The proposed moderation model was tested using cross-sectional data from the first month following return from deployment, and at 6 months and at 12 months post-deployment. Results showed that dysphoria symptoms significantly moderated relations between intrusions and total drinking days and heavy drinking days at one month post-deployment; however, a significant pattern was not demonstrated at 6 months and 12 months. Further, dysphoria did not moderate the relation between intrusion symptoms and drinks per drinking day at the three time points. Theoretical and clinical implications are subsequently discussed. Highlights: We examined dysphoria's moderating role between intrusions and alcohol use. Sample was 127 trauma-exposed Veterans following deployment to Iraq or Afghanistan. Assessments were conducted at baseline, 6 months, and 12 months post-deployment. Dysphoria moderated relations between intrusions and total/heavy drinking days. Dysphoria did not moderate relations between intrusions and drinks per drinking day. Significant moderating results were obtained only at one month post-deployment. Intrusions predict alcohol use at higher levels of dysphoria.